Identifikasi Mission Drift Pada Keadilan Jender dan Inklusi Sosial di Lembaga Keuangan Mikro Syariah - Hazmi, Faiqul; Utami, Cahyaning Budi (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
Islamic Microfinance institutions (IMFIs) their operations are expected to not only consider financial performance, but must accommodate the principles of gender justice, because humans both men, women and people with disabilities are equally as khalifatullah fil ard to manage the earth as God wills. However, several studies show a shift in the mission carried out by IMFIs. This research aims to determine the forms of mission drift that occur at IMFIs, especially Baitul Maal Wat Tamwil in 3 districts in Central Java, District of Jepara, Kudus and Demak. These three regions were chosen because they have different levels of IMFIs development. The research results show that the forms of mission drift that occur include: (1) Differences in the accessibility of financial services based on gender; (2) Changes in IMFIs customer priorities; (3) Product changes that prioritize bankable customers; (4) Increasing of Margin, Ujroh profit sharing portion and costs; (5) Changing the focus of financing to be more profit-oriented. The implication of the results of this research is that MFIs need to mainstream gender by paying attention to the portion of financing and absorbing public funds in a Gender-equity manner by encouraging balance between the portions of men and women. Regulators need to carry out strict supervision so that their commitment to maintaining the IMFIs mission values, apart from that, stimulus to institutions that prioritize gender justice also needs to be provided.